Position paper on the challenges posed by modern applications to cyber-physical systems theory. (November 2019) - Allgöwer, Frank; Borges de Sousa, João; Kapinski, James; Mosterman, Pieter; Oehlerking, Jens; Panciatici, Patrick; Prandini, Maria; Rajhans, Akshay; Tabuada, Paulo; Wenzelburger, Philipp
Abstract: Cyber-physical systems theory offers a powerful framework for modeling, analyzing, and designing real engineering systems integrating communication, control, and computation functionalities (the cyber part) within a natural and/or man-made system governed by the laws of physics (the physical part). New methodological developments in cyber-physical systems theory are required by traditional application domains such as manufacturing, transportation, and energy systems, which are currently experiencing significant and – to some extent – revolutionary changes to address the needs of our modern society. The goal of this position paper is to provide the cyber-physical systems community, and especially young researchers, a clear view on what are research directions worth pursuing motivated by the challenges posed by modern applications.